Climatological Characteristics of Cold Fronts and Their Impacts on Air Quality in Cold Seasons Over the Eastern China. Issue 22 (15th November 2022) - Xue, Lian; Zhou, Derong; Huang, Xin; Lou, Sijia; Ding, Aijun
Abstract: Eastern China has been frequently suffering from air pollution problems in the past decades. Besides the intensive emissions, weather‐system evolution is generally regarded as an important factor influencing air quality, among which cold fronts are of great importance in regulating the synoptic‐scale variations of regional pollution. Despite numerous case studies conducted, the long‐term climatological behaviors of cold front depicting their overall impacts on air quality remain unrevealed. In this study, an objective front identification approach has been performed to construct a 42‐year climatology of cold‐front activities in eastern China. It is found that the cold fronts and pollution events usually coincide in cold seasons, and have great impacts on air quality in metropolitan regions. A significant accumulation (cleansing) effect on surface air pollutants in the Beijing‐Tianjin‐Hebei (BTH) region before (after) the passage of the front has been observed in autumn and winter, with mean fine particles (PM2.5 ) concentrations varying by 40–80 μg/m 3 during the processes. The cold fronts that go through the Yangtze River Delta region in winter also lead to the decrease of the PM2.5 concentration after the passages of about 15 μg/m 3 . Major influencing factors include the changes in meteorological conditions and regional transport driven by frontal circulation, which are favorable for pollutants dispersion and advection. On the interannual scale, the cleansing effect of the cold fronts dominates in BTH regions. The statistical relationship between cold fronts and regional air quality highlighted would help understand the impact of both past and future climate on regional pollution from a synoptic perspective. Plain Language Summary: Air pollution has great adverse impacts on human health and societal activities. As one of the most populated and emission‐intensive regions around the world, eastern China has been suffering from severe haze pollution in recent decades, especially in cold seasons. Cold fronts are identified as strong weather systems that could have great impacts on regional air quality in autumn and winter over eastern China, according to previous case studies. In this work, an automated method was used to detect cold fronts from a gridded meteorological data set for the period 1980–2021, by which the relationship between air quality of the three largest city clusters in eastern China and the cold front activities has been established. It is found that for cities in northern China, years with more cold fronts would have cleaner winters. While for southern China cities, the cold fronts usually come with polluted air masses, which would deteriorate the local air pollution. This study highlights a unique perspective on understanding the weather and climate impacts on regional air quality. Key Points: The cold fronts over eastern China are most active in cold seasons, especially in mid‐latitudes Significant accumulating and cleaning of particulate matter occurs when cold fronts pass Beijing‐Tianjin‐Hebei and Yangtze River Delta as averaged for multiple cases Major influencing factors include the changes in meteorological conditions and regional transport during cold front passage